Changes of polyphenol, anthocyanin and rutin content in sour cherry varieties during ripening - Kállay, Erzsébet (Acta Biologica Szegediensis, 2008)
In our experiments we studied the variation of inner content values in connection to ripening time in the case of four tart cherry varieties (Prunus cerasus L.). Our aim was to optimize the harvest time on the base of antioxidant capacity. The experiments were carried out in orchards of the Research Institute for Fruitgrowing and Ornamentals in Érd-Elvira major (varieties ’Érdi bőtermő, ’Kántorjánosi 3’) and in orchards of the Agárd Frucht Ltd. in Agárd (varieties ’Érdi jubileum’, ’Maliga emléke’). Anthocyanin, polyphenol and rutin content of fruits were investigated in laboratory. According to the results it can be stated, that in case of the studied varieties the optimal harvest time for industrial processing is the second picking. At this time the anthocyanin, polyphenol and rutin contents of varieties are suitable. In general, at the end of maturity period the fruits shrink, fruit weight and juicity decreases in consequence of water loss, therefore determining optimal harvest time for the desired utilization purpose is very important. According to our results, among the four studied varieties, ‘Érdi jubileum’ has the highest values regarding polyphenol as well as anthocyanin and rutin contents.